A Quest towards Eccentric Piedfort Pairs. Issue 17 (3rd May 2018) - Mehrotra, Sonam; Raje, Sakthi; Jain, Anant Kumar; Jain, Ankit; Kandasamy, Parameswaran; Butcher, Ray J.; Angamuthu, Raja
Abstract: A group of symmetrically‐trisubstituted‐1, 3, 5‐triazine‐based molecules have been studied extensively in order to create Piedfort pairs that are intended to be employed in sequestration of small molecules. Extensive inter and intramolecular interactions observed in the solid‐state of the studied triazine molecules lead to the formation of one‐dimensional ribbon and two‐dimensional sheet motifs. Koneramine formation was applied as a new strategy to increase the bulkiness of the substituents on 1, 3, 5‐triazine ring that prevented the formation of ribbons and sheets yet yielded hydrogen‐bonded dimer. The protonated forms of one of the triazine compound showed that the triazine ring nitrogens are more basic than amine nitrogens on the periphery; protonated N 2, N 4, N 6 ‐triphenyl‐1, 3, 5‐triazine‐2, 4, 6‐triamine resulted in eccentric Piedfort pairs that displayed aesthetic structural patterns possessing variety of inter and intramolecular interactions including stacking between electron deficient triazine ring of one member and electron rich aryl ring of another member. Abstract : Controlling the architectures of triazine based molecules yields many aesthetic solid‐state structures including one‐dimensional chains, two‐dimensional sheets and hydrogen‐bonded dimers; eccentric Piedfort pairs of electron‐rich and electron‐poor aromatic rings have been formed. Konermine formation was used as a new strategy to increase the bulkiness of substituent on the triazine ring that prevented the formation of ribbon motif.